FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT UNTUK TETAP TINGGAL DI DAERAH RAWAN BANJIR NAGARI API-API PASAR BARU KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Rukmana, Faradila - (STKIP PGRI Sumbar, 2014)
The purposes of this study is to obtain information, analyze , and discuss about the factors that influenced the people to remain living in flood-prone areas at Api Api Pasar Baru Village, Bayang Sub-district, Pesisir Selatan District. The type of this research is descriptive quantitative research. The sample selection in this study using two methods, namely purposive sampling that used to designate only the affected areas by flooding in which consists of Muara Api Api village and Api Api Market and propotional random sampling method that used to know about amount of the research population with a proportion of 25% , so the sample amounted to 104 house holds. The sources of the data from this study are the primary data and secondary data with the data collection tools through direct interviews and using questionnaires. Based on a simple linear regression analysis, multiple and correlation it can be concluded as follows: (1) strategic location that influence people to remain living in flood-prone areas at Api Api Pasar Baru Village, Bayang Sub-district, Pesisir Selatan District, with a contribution of 21,1%, (2) economic factors that influence people to remain living in flood-prone areas at Api Api Pasar Baru Village, Bayang Sub-district, Pesisir Selatan District, with a contribution of 9,7%, (3) communal land that influence people to remain living in flood-prone areas at Api Api Pasar Baru Village, Bayang Sub-district, Pesisir Selatan District, with a contribution of 8,2%, (4) the government efforts to reduce the risk of flood does not have effect to the people to remain living in flood-prone areas at Api Api Pasar Baru Village, Bayang Sub-district, Pesisir Selatan District, with a contribution of 0,6%, (5) strategic location, economic factors, communal land and the government efforts to reduce the risk of flood simultaneously influence people to remain living in flood-prone areas at Api Api Pasar Baru Village, Bayang Sub-district, Pesisir Selatan District, with a contribution of 35%.